Predictors of Cardiac Arrest in Patients with Acute Myocardial Infarction in Singkawang City - Suhendra Suhendra; Teguh Wahju Sardjono; Laily Yuliatun; Kelana Kusuma Dharma (Universitas Aisyah Pringsewu, 2021)
The current nursing literature has not devoted adequate attention to studying cardiac arrest in hospitals, especially in patients with acute myocardial infarction. Identifying predictors of cardiac arrest in patients with acute myocardial infarction is needed to determine appropriate nursing strategies to prevent cardiac arrest. This study aims to determine the predictor factors of cardiac arrest in patients with acute myocardial infarction. This study used a retrospective cohort design with a population of 181 people who were treated with a diagnosis of STEMI and NSTEMI during 2017-2020. Data analysis using chi-square test, Spearman rank and logistic regression. Spearman rank analysis test, age p=0.045, r=0.149; systolic pressure p=0.002, r=-0.228; diastolic pressure p=0.020, r=-0.173; Heart rate p=0.064, r=0.138; the number of comorbid diseases p = 0.322, r = 0.074 and Killip class p = 0.000, r = 0.431. Chi-square analysis test, gender p=0.487, OR=1.322; ECG picture p=0.885, OR=1.060; troponin enzyme levels p=0.951, OR=1.025; and length of stay p=0.000, OR=0.181. The predictor factors for cardiac arrest in patients with acute myocardial infarction were Killip class, length of stay, systolic pressure and heart rate. The most dominant factor in influencing cardiac arrest in patients with acute myocardial infarction is the Killip class.Abstrak: Literatur keperawatan saat ini belum mencurahkan perhatian yang memadai dalam mempelajari henti jantung di rumah sakit khususnya pada pasien infark miokard akut. Mengidentifikasi factor predictor henti jantung pasien infark miokard akut diperlukan untuk menentukan strategi keperawatan yang tepat dalam mencegah kejadian henti jantung. Penelitian ini bertujuan untuk mengetahui factor prediktor kejadian henti jantung pada pasien infark miokard akut. Penelitian ini menggunakan desain cohort retrospective dengan populasi sebanyak 181 orang yang dirawat dengan diagnosis STEMI dan NSTEMI selama 2017-2020. Analisis data menggunakan uji chi-square, spearman rank dan regresi logistik. Uji analisis spearman rank, usia p=0.045, r=0.149; tekanan sistolik p=0.002, r=-0.228; tekanan diastolik p=0.020, r=-0.173; Heart rate p=0.064, r=0.138; jumlah penyakit komorbid p=0.322, r=0.074 dan kelas Killip p=0.000, r=0.431. Uji analisis chi square, jenis kelamin p=0.487, OR=1.322; gambaran EKG p=0.885, OR=1.060; kadar enzim troponin p=0.951, OR=1.025; dan lama rawat p=0.000, OR=0.181. Factor predictor kejadian henti jantung pada pasien infark miokard akut adalah kelas Killip, lama rawat, tekanan sistolik dan heart rate. Factor paling dominan dalam mempengaruhi henti jantung pada pasien infark miokard akut adalah kelas Killip.